أثر التقدم التكنولوجي في خلق الفجوة التقنية - صقر محمد; شرف سمير; غدير باسم غدير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يقدم هذا البحث دراسة لإشكالية الفجوة التقنية العالمية والتي كان سببها التطور التكنولوجي المتسارع. فقد تم رصد أطراف تلك الفجوة التقنية في أقاليم عدة منها الفجوة التقنية ما بين بلدان العالم، ومن ثم دراسة الفجوة التقنية ما بين الإقليم العربي والأقاليم الأخرى في العالم. وزيادةً في التحديد تم دراسة مؤشرات الفجوة التقنية بين البلدان العربية. إن الفجوة التقنية قسّمت العالم إلى أغنياء تكنولوجياً وفقراء تكنولوجياً، مما انعكس على الحياة الاجتماعية والاقتصادية والثقافية بين أطراف الفجوة. وإننا إذ نعرض هذا البحث لنبين أسباب تلك الفجوة ونتائجها ومحاذيرها وكيفية التعامل معها بالنسبة للبلدان العربية ممثِّلةً للبلدان النامية. إن تلك الفجوة تطرح إشكالية مَنْ يُنتج ومن يستهلك حتى غدت البلدان النامية مستهلكاً كبيراً لكل منتجات التكنولوجيا من البلدان المنتجة مما حوّل تلك البلدان النامية إلى سوق واسعة للتصريف ويكاد نمط الاستهلاك غير الرشيد يسيطر عليها بعيداً عن مسألة البحث عن نقل التكنولوجيا وتوطينها بأساليب اقتصادية ناجعة. This research is a study for the problem of international technical gap, which was caused by the increasing technological development. Sides of this gap were observed in many regions of the world, then the study of the technical gap between the Arabic region and other regions in the world. In order to be more precise, we have studied the parameters of the technical gap between the Arabic countries. This technical gap has divided the world into technologically rich, and technologically poor, which was reflected on the social, economic and cultural life on the sides of the gap. In this research we explain the reasons of this gap, its results, forewarnings and the way of its handling for the Arab countries as representatives of the developing countries. This gap presents the problem of who produces and who consumes, so that the developing countries became great consumers for all the technological products in the producing countries, which changed these countries into a big market for marketing, and are almost controlled by the type of western consumption, regardless of the matter of transforming technology and settling it successfully by economical means.